PERSEPSI WARGA BELAJAR TERHADAP PEMBELAJARAN DI LEMBAGA KURSUS BAHASA INGGRIS MRJ ENGLISH HOUSE JALAN BINA KRIDA KELURAHAN TAMPAN KOTA PEKANBARU - Ade Syntia; Jasfar Jas; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the perceptions of learners on learning in English language course institutions MRJ English House Binakrida street Kelurahan Tampan Kota Pekanbaru. The formulation of the problem in this research is whether the perception of the learning community on the learning of English language course institution of MRJ English House has been considered good. The type of this research is descriptive with quantitative approach that aims to describe the results of research with numbers. Number of population as many as 50 people then the researcher use saturated samples then all the population sampled as many as 50 people studying in English language course institution MRJ English House Jalan Bina Krida Kelurahan Tampan Pekanbaru City. And 20 people tested in Institute ICC course Pekanbaru City. Technique of collecting data in this research is questionnaire which amounts to 55 item statement conducted 5 questionnaire erdapat experiments that are not valid then peneli throw it into 50 statement for research. The result of data analysis shows that the perception of the students learn tehadap learning in English language course institution MRJ English House Binakrida street Kelurahan Tampan Pekanbaru city is very good with the percentage of overall 88.9% means the perception of learning to learn very good. Can be concluded among the 7 indicators are very dominant facilities and infrastructure with sub-indicators of learning facilities that have covered the place of learning, teaching materials, internet and other learning facilities with a percentage of 97.33. Keywords: Perception of studying residents, Learning, course institutions.